Management Strategy for Hydroelectric Project Toro 2: Knowing and enhancing natural resources sustainably - Pereira Chaves, José (2014)
The aim of this article is to understand and sustainably enhance the biological and ecological resources of the Hydroelectric Project of Toro 2, thus; a research was carried out to inventory the presence of birds, mammals and plants, in order to know if the site qualifies as a biological tourist attraction, as well as to know the opinion of local people. It is proposed the sustainable uses of natural resources, through a strategy of use, management and conservation of the ecosystems.